Henri Michaux's program for the psychedelic humanities - Davis, Oliver (Frontiers in Psychology, 2023)
This article presents an analytical reading of the extraordinarily rich cultural production around drugs by the twentieth-century French poet, writer, critic and visual artist Henri Michaux (1899–1984). Over about a decade, from the mid-1950s, the otherwise habitually sober Michaux wrote five books, included within which were dozens of drawings, and made one half-hour film, charting his adventures as an initially reluctant yet persistent psychonaut, principally with mescaline, but also with psilocybin, LSD and cannabis. This has rightly been described as one of the most creative cultural explorations of mescaline. It is more extensive, texturally complex and aesthetically demanding than Aldous Huxley’s far better known near-contemporaneous published work on psychedelics in English, which are well known within and arguably foundational for psychedelic studies. Yet this very complexity, as well as the national-linguistic context of its articulation – there was no mass psychedelic counterculture in France – has limited wider engagement with it. I argue that Michaux’s aesthetic reconstruction of psychedelics’ effects on his creative brain can be read as a ‘programme’ for the emerging field of the psychedelic humanities and that they make a substantial contribution, which I sketch in outline here, to the following of its core concerns: (1) the role of psychedelics in enhancing ‘creativity’; (2) conceptualization of the politics of psychedelics; (3) the meaning and value of psychedelic mysticism. I aim to show that Michaux’s work on drugs has much to contribute to cultural understanding of psychedelics today and accordingly that this unjustly neglected classic of French – and global – drug culture deserves to be far better known.